Dynamic Simulation Analysis of the Antiswing Device for Ship-Mounted Batch Transfer Hanging Basket - Jianli Wang; Haolin Li; Shenghai Wang; Haiquan Chen; Yuqing Sun (Applied Bionics and Biomechanics)
When the rescue vessels use the hanging basket to transfer the wounded at sea, under the action of waves, the ship causes the hanging basket to swing significantly. To prevent the second injury to the wounded caused by the large swing of hanging basket, a rope-driven rigid-flexible hybrid hanging basket antiswing control system is designed, the control principle of the system is introduced, and an accurate dynamics model of the system is established based on the D’Alembert principle, the rigid-flexible hybrid model is used to the antiswing control and simulation of the ship-mounted batch transfer hanging basket for the first time. Analyzed its control principle and simulate the variations in length, velocity, acceleration, and force changes of the control ropes. By installing rigid bal-hinge telescopic sleeve, the simulation results indicate that the indicators of the driving ropes are smooth and continuous and the value changes are also within a suitable range. The force on the four control ropes has been reduced by ∼24.1%, 23%, 26.4%, and 25.1%, resulting in the force that is more reasonable and enhancing the safety of hanging basket system. The hanging basket antiswing device is capable of compensating for rolling and pitching motions at sea and has a strong impact on swinging.